Penggunaan Semut Hitam dan Bokashi dalam Peningkatan Resistensi dan Produksi Tanaman Kakao - Armaniar Armaniar; Ahamad Saleh; Fachrina Wibowo (AGRIUM: Jurnal Ilmu Pertanian, 2019)
Cocoa is the source of life for more than 6.5 million farming families. Cocoa farmers in Langkat District about 2081 with an area of 2603/ha. Cocoa production in Langkat recorded about 950 kg/ha/year, but some produced about 450 kg/ha/year. In addition to the shortage of subsidized inorganic fertilizers, another problem in Indonesia’s low cocoa production especially Langkat is because cultivation was not done.Another, the attack of plant-disturbing organisms, such as Cocoa Borer (CPB) and Vascular Streak Dieback (VSD). Cocoa pod borer, Conopomorpha cramerella is a very serious pest and 80% production reduced. It was because the cocoa pod borer is difficult to control and had spread throughout Langkat. By 2018, cocoa production in Langkat about 7 kg/weeks. Biological control using black ants has been developed as a natural CPB pest agency by making ant nest of 30-40 strands of dried cocoa leaves with permanent polystyrene plastic or dry cocoa leaves and tied with rafia straps. The results showed that cocoa pods were heavy damaged under 5%.  Fertilizing with Bokashi which are made of cocoa leaves, bran, husks and manure fermented with EM-4 was applied 5 kg/tree, for plant resistance to VSD disease and cocoa production increased. Farmer are commitment to their respective cocoa gardens and hope they can produce organic cocoa in the future